IMPLEMENTASI SISTEM INFORMASI MANAJEMEN TERINTEGRASI DI SMP PLUS DARUSSALAM - Hasanah, Uswatun; Aimah, Siti (Institut Nahdlatul Ulama Tasikmalaya, 2025)
In the digital era, SIMPT is expected to improve efficiency, transparency, and accountability in managing educational data and information. This study aims to analyze the effectiveness and complexity of the implementation of the Integrated Education Management Information System (SIMPT) in educational institutions, especially in SMP Plus Darussalam. This study uses a qualitative approach with observation methods and in-depth interviews with stakeholders, such as principals, administrative staff, and teachers who use the system. This study will analyze: Improving Administrative Efficiency and Decision Making, Positive Impact on Learning and Communication Quality, Importance of User Training and Support, and Influence of Leadership and Organizational Culture. The results of the study indicate that SIMPT has great potential in supporting school administration processes more efficiently, reducing data duplication, and accelerating the flow of information. However, its implementation is not without challenges. Some of the main obstacles found include limited technological infrastructure, such as unstable internet networks, low digital literacy of some users, and resistance to changing manual to digital systems. In addition, the need for ongoing training for system users is also an important factor in supporting successful implementation. Therefore, a strategy is needed to strengthen user capacity, policy support, and improve infrastructure to ensure the sustainability and effectiveness of SIMPT in the long term.